Luminescence Nanomaterials and Applications (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue reprint covers the synthesis of luminescent nanomaterials, applications for in vitro and in vivo imaging, detection based on fluorescence resonance energy, and the applications of luminescent nanoparticles for photodynamic activation and solid-state displays, as well as new materials and structures, such as perovskite quantum dots, and novel phenomena, such as aggregation-induced emissions. In total, there are 15 papers (2 reviews and 13 research articles) in this Special Issue consisting of the major areas of upconversion of luminescent nanomaterials; luminescent nanomaterials for solid-state lighting, displays, and anti-counterfeiting; particle-based sensing technology; particle-based therapeutics; and new materials and structures. This Issue represents new developments in luminescence nanotechnology.